The Role of Per Oral Cholangiopancreatoscopy (POCPS) in Complicated Pancreaticobiliary Disease - Ari F Syam; Syahidatul Wafa; Dadang Makmun (Acta Medica Indonesiana)
A fifty-five year old female patient presented with jaundice, subfebrile fever and dark yellow urine since one month before admission. She lost weight 10 kilograms during one month. One day before admission to Ciptomangunkusumo General Hospital, she complained of worsened abdominal pain at right upper quadrant urging her to come to the emergency room. An abdominal examination revealed Murphy sign, mild hepatomegaly and deeply icteric sclera. Serum bilirubin was 21.8 mg/dl, alkaline phosphatase and gamma-glutamyltransferase levels were significantly elevated (1090 IU/L and 560 IU/L consecutively) while the transaminases were moderately high (ALT 80 U/L). The C-reactive protein was 555 mg/L. An abdominal ultrasound examination revealed dilatation of right and left intrahepatic bile duct and presence of common hepatic duct stone. Subsequent magnetic resonance imaging/ magnetic cholangiopancreatography (MRI/ MRCP) revealed intrahepatic bile duct dilatation, multiple CBD stone and benign stricture at common hepatic duct causing right and left intrahepatic bile duct obstruction.We assessed the patient as acute cholangitis and obstructive jaundice suspected to be caused by biliary duct stone then we performed endoscopic retrograde cholangiopancreatography (ERCP), we revealing stenosis at distal CBD, multiple CBD stone, giant stone in CHD and dilatation of bilateral IHBD. We performed CBD stone extraction then inserted biliary stent for drainage. Then we planned to do second ERCP with SpyGlassTM for giant stone extraction. After the first ERCP, the clinical condition of the patient improved and the bilirubin decreased to 10 mg/dL. In the next two weeks we performed a second ERCP to extract the giant stone with SpyGlass TM. However, after we inserted SpyGlassTM into the biliary duct, what we found were not as we expected before. We revealed that there was a mass in biliary duct and there was no CBD stone. We did the biopsy and inserted a new plastic stent (after removed the older one) to the common biliary duct. Surprisingly, the result of histopathology also supports our findings, which was the adenocarcinoma at common bile duct.